Revision of the family Carabodidae (Acari: Oribatida) X. Bovicarabodes jacquelinae sp. nov., redefinition of the genus Tuberocepheus Balogh & Mahunka, 1969 and redescription of Tuberocepheus longus (Balogh, 1962) - Fernández, Néstor Alfredo (2016)
Bovicarabodes jacquelinae sp. nov. is easily differentiated from other congeners by paired rounded to ovate prodorsal cavity with internal ovoid incision; presence of medial eye pillar; two cuticular ridges anterior to interlamellar setae; and incomplete bothridial ring with bothridial tooth. Notogastral anterior depression ovoid, with two posterior semicircular zones delimited by prominent furrow; notogastral anterior depression extending to beyond c2 and da setae. Tutorium a strongly curving cuticular thickening; humeral apophysis elongate; small triangular discidium. Genital opening smaller than anal opening; aggenital and ad3 setae in close proximity. B. jacquelinae is similar to B. deharvengi, differentiated principally by shape and position of elevated interlamellar process; position of interlamellar setal insertion; notogastral anterior depression; and shape of humeral process. Tuberocepheus longus (Balogh, 1962) is redescribed, with clarification being obtained by the use of optical and scanning electron microscopy. The genus is characterized by the combination of the following characters: Prodorsum divided into two ear-like processes; shallow lamellar furrow not clearly delimited; smooth narrow bothridal ring; bothridial tooth a finger-like projection; and conspicuous polyhedral posterior prodorsal depression. Notogaster 12 pairs of setae; seta c absent; medium-sized elevated zone situated between notogastral anterior depression and notogastral posterior depression; two pairs lateral paired elevations; three pairs central paired elevations; pedotectum I larger than tutorium. Epimeres poorly delimited; anterior genital furrow simple, lacking lateral depression; well-developed depression surrounding genital opening; depressions surrounding genital opening and anterior genital furrow connected by a narrow channel; anal opening larger than genital opening.